Morphophysiological analyses on Teak (Tectona grandis Linn. f.) from three provenances. (February 2019) - Larekeng, S H; Gusmiaty,; Restu, M; Arsyad, M A; Dermawan, R
Abstract: High genetic diversity in teak species causes problems in identifying the individuals. To identify the characteristics of the individuals, an identification system using morphophysiological analyses for Teak is needed. This study was aimed to identify the morphological and physiological differences between three different teak provenances, i.e., Cepu, Sidrap, and Bau-bau provenances. The research was carried out by observing morphological characteristics, i.e., leaf characteristics (color, shape, venation pattern, margin, base, tip, and surface texture) and tree characteristics (height and diameter), and physiological characteristics (leaf area, chlorophyll content, and leaf water content). There were five leaf colors observed in the analysis (green- brownish, green-yellowish, green, dark green, and green with yellow spots). Leaf shapes were divided into two shape types, i.e., widened ellipse and inverted oval. Flat leaf margin, tapered leaf tip, and base, rough surface texture, pinnate venation pattern were observed on all evaluated leaves. Height and diameter of trees were higher in Bau-bau provenance than other provenances. Leaf area was affected by provenance but not leaf position in provenance. Chlorophyll content was affected by both provenance and leaf position, whereas water content was only affected by leaf position in provenance.